Management of ecofriendly practices with the environment in supermarkets: a perception of university students and managers - Véliz, Tomás (2020)
Companies focus on eco sustainability and their contribution to sustainability is aimed at rethinking new practices for ecological products and waste disposal, committed to the environment. Objective: To describe and interpret the management of ecofriendly practices in supermarkets, based on the perception of university students and managers, to contribute towards a model of responsible culture management with the environment in organizations. Method: Qualitative-quantitative, mixed approach, non-experimental design, descriptive and interpretive type. It shows 93 university students and 02 managers, a cross-sectional survey and in-depth interviews. Results: The management of ecofriendly practices in supermarkets is comprehensively rated as regular with 37% according to the perception of university students; the management of waste energy and water qualifies regular with 30%, requires attention as centers of new income and reduction of expenses. Conclusion: The construction of the empirical bases of the ecofriendly management model are: Products, packaging and eco-labels. Waste, energy and water. Environmental communication and infrastructure.